Teachers' Ability to Stimulate Children's Development Reviewed from the Status of Educators in TK Ngemplak District - Alamsyah, Evi Nur; Darsinah, D (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study examines how kindergarten teachers’ educational qualifications in Ngemplak District relate to their ability to stimulate children’s developmental progress, aiming to determine whether higher educational status corresponds to more effective early childhood stimulation techniques. Methodology: Employing a quantitative descriptive design, the research collected data via structured questionnaires administered to kindergarten teachers across the Ngemplak area. Questions focused on teachers’ highest educational attainment and the specific methods they use to foster cognitive, social, emotional, and motor development in their students. Statistical analysis then compared stimulation‑method proficiency across differing education levels. Results: Findings reveal a clear, statistically significant association between teachers’ educational backgrounds and their stimulation effectiveness. Educators holding advanced qualifications demonstrated a deeper understanding of developmentally appropriate practices—such as targeted play activities, scaffolding techniques, and differentiated instruction—whereas those with lower formal training exhibited less varied and less responsive approaches. Applications/Originality/Value: By highlighting the pivotal role of teacher education in enhancing early childhood stimulation, this study underscores the need for targeted professional development and credentialing programs within Ngemplak District. Its insights can guide policymakers and school administrators in prioritizing higher-education pathways and in‑service training to ensure all kindergarten teachers are equipped with the pedagogical tools necessary to optimize children’s developmental outcomes.